Intralesional bleomycin: A treatment modality for conjunctival lymphangioma - Bansal, Smriti (Oman J Ophthalmol, 2020)
Lymphangioma is a benign hamartomatous lesion of vascular system which frequently involves orbit and ocular adnexa. A 35-year-old male patient presented with a subconjunctival mass extending from limbus to fornices. There was a history of recurrent swellings following episodes of upper respiratory tract infection. Bleomycin is an antineoplastic agent which acts on endothelial cells of the vascular channels, helps in collapsing the cystic cavity, and prevents its recurrence. We report a case where only bleomycin injection has been used intralesionally at multiple spots and patients have shown good cosmetic outcome without any recurrence noted after 1 year of follow-up.